Implementation of Archives Digitization as a Measure to Preserve and Enhance Access to Information - Nur Laili Indah Fuji Lestari; Handari Niken Anggraini; Hendro Margono (Universitas Lambung Mangkurat, 2026)
Archive digitization is a strategic step in modern information management, especially in response to the challenges of preserving physical documents and the increasing public demand for fast, efficient, and easily accessible information. Dinas Perpustakaan dan Arsip Daerah (DPAD) Daerah Istimewa Yogyakarta (DIY) is one of the institutions responsible for managing regional archives and has implemented digitization as part of the archive preservation process. This activity aims to examine the implementation of community service activities through field study practice at DPAD DIY, focusing on archiving institutional challenges and the application of digital technology in archive management. The methods used in this activity refer to the service-learning model and include observation and interviews, preparation, implementation, and evaluation. The evaluation reviews the process and results, highlighting effective aspects and identifying any obstacles or shortcomings. The instruments used in the evaluation process include observation and interview results, field notes, documentation, and literature review. The results show that the activity contributed directly to archive digitization, including 4-5 audiovisual recordings per day, more than 1,000 photo archives in 167 digital files within six working days, and one box of textual archives consisting of 37 files converted into digital format. These outputs support better archive preservation and improve access to information. However, several obstacles were also found, such as limited, outdated equipment, insufficient human resources compared to the volume of archives, and inadequate workspace conditions. Nevertheless, this activity made a real contribution to the digitization process and produced recommendations for improvements to support the sustainability of the archive media transfer program at DPAD DIY.